Evidence for a continuous drift of the HIV-1 species towards higher resistance to neutralizing antibodies over the course of the epidemic. - Mélanie Bouvin-Pley (Public Library of Science (PLoS), 2013)
We compared the neutralization sensitivity of early/transmitted HIV-1 variants from patients infected by subtype B viruses at 3 periods of the epidemic (1987-1991, 1996-2000, 2006-2010). Infectious pseudotyped viruses expressing envelope glycoproteins representative of the viral quasi-species infecting each patient were tested for sensitivity to neutralization by pools of sera from HIV-1 chronically infected patients and by an updated panel of 13 human monoclonal neutralizing antibodies (HuMoNAbs). A progressive significantly enhanced resistance to neutralization was observed over calendar time, by both human sera and most of the HuMoNAbs tested (b12, VRC01, VRC03, NIH45-46(G54W), PG9, PG16, PGT121, PGT128, PGT145). Despite this evolution, a combination of two HuMoNAbs (NIH45-46(G54W) and PGT128) still would efficiently neutralize the most contemporary transmitted variants. In addition, we observed a significant reduction of the heterologous neutralizing activity of sera from individuals infected most recently (2003-2007) compared to patients infected earlier (1987-1991), suggesting that the increasing resistance of the HIV species to neutralization over time coincided with a decreased immunogenicity. These data provide evidence for an ongoing adaptation of the HIV-1 species to the humoral immunity of the human population, which may add an additional obstacle to the design of an efficient HIV-1 vaccine.